Company Profile Kantor Camat Talang Kelapa Kabupaten Banyuasin - Fadillah, Ridho Akbar; Ariati, Nining; Dhamayanti, Dhamayanti (Jurnal Nasional Ilmu Komputer, 2024)
A company profile website is a website that displays information about the company's background, products or services, contact information, and brief news about the company. The Talang Kelapa Sub-District Office already has a website to convey information. Still, no administrative services can be done online on the website, so the community must come directly to the Talang Kelapa sub-district office to carry out administrative services. Due to the lack of information, many people need to learn about the Service Information and Profile of the Talang Kelapa Sub-District Office. With this situation, the researcher is interested in compiling this research activity by taking the title "Company Profile of the Talang Kelapa District Office, Banyuasin Regency." It is hoped that the Information System will make it easier for people to get information about the profile of the Talang Kelapa District Office. Using the PHP programming language and MySQL database. The software development method used in this research is the prototype method. System testing will be carried out using the black box testing method.